Of Fitness for Work to Professionalism: Psychological and Pedagogical Conditions - Milkov, Luchian (Research Papers, 2016)
Profession and practice occupy about 50% of human life in modern developed societies. In Bulgaria the percentage is even greater, due to the relatively low life expectancy for men and women. We believe that because it is a mistake to lose so many years, funds, intellectual, mental and physical energy to a profession that does not bring satisfaction to the individual. The correct choice of profession allows to realizing their own potential, to avoid disappointment, to ensure equity and family life financially. Every profession, even the most interesting and beloved requires effort, tension.